Ocean Climate Monitoring - Cole, Rick; Kinder, Jeff; Yu, Weidong; Ning, Chun Lin; Wang, Fujun; Chao, Yang (Frontiers in Marine Science, 2019)
Measuring ocean physics and atmospheric conditions at the sea-surface has been taking place for decades in our world’s oceans. Enhancing R&D technologies developed in Federal and academic institutions and laboratories such as WHOI’s Vector Averaging Current Meter (VACM, 1970s) and NOAA – PMEL’s: Autonomous Temperature Line Acquisition System (ATLAS, 1980s) as example, in-situ ocean measurements and real-time telemetry for data processing and dissemination from remote areas of oceans and seas are now common place. A transition of this “ocean monitoring” technology has occurred with additional support from individual and group innovative efforts in the field of ocean instrumentation. As a result, long-term monitoring of ocean processes and changes has become more accessible to the research community at large. Here; we discuss a “Hybrid” air-sea interaction deep-sea monitoring system that has been developed in the private sector to mirror ocean-climate community data streams and has been successfully deployed on three basin-scaled programs in the Indian Ocean (RAMA, First Institute of Oceanography, FIO, China), the Andaman Sea (MOMSEI, Monsoon Onset Monitoring, FIO) and the Pacific Ocean (China’s Institute of Oceanology, Academy of Sciences research in the western tropical Pacific). This application is a base to build upon as new sensors are developed and increased sampling at higher resolutions is required. A multidisciplinary tool to add new biological and biogeochemical sensors to study interaction with the physical processes of our oceans. This application can also be used at FLUX sites to enhance the Argo Program, telemetry docking stations for autonomous vehicles such as sail-drones, gliders and wave riders for enhancement and contribution to the Global Tropical Moored Buoy Array (GTMBA), Global Ocean Observing System (GOOS), Global Climate Observing System (GCOS), and the Global Earth Observing System of Systems (GEOS).